2020
DOI: 10.1002/adhm.202000198
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable Thioether Grafted Hyaluronic Acid Nanofibrous Hydrogel for Synergistic Modulation of Inflammation Microenvironment to Accelerate Chronic Diabetic Wound Healing

Abstract: Current standard of care dressings are unsatisfactorily inefficacious for the treatment of chronic wounds. Chronic inflammation is the primary cause of the long‐term incurable nature of chronic wounds. Herein, an absorbable nanofibrous hydrogel is developed for synergistic modulation of the inflammation microenvironment to accelerate chronic diabetic wound healing. The electrospun thioether grafted hyaluronic acid nanofibers (FHHA‐S/Fe) are able to form a nanofibrous hydrogel in situ on the wound bed. This hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 54 publications
1
103
0
Order By: Relevance
“…27 More recently, thioether-functionalized hyaluronic acid was electrospun into nanofibres and formed fast-resorbing hydrogels that were highly antioxidant, anti-inflammatory, and significantly promoted wound closure/healing in a diabetic wound model. 28 These data lend support for the expanded use of polysulfides/ PPS as anti-inflammatory agents in topical wound-healing applications. However, slow-degrading crosslinked hydrogels and nanoparticle dispersions are not ideal for inflammatory skin disorders with a more diffuse skin coverage, such as chronic wounds (e.g.…”
Section: Introductionmentioning
confidence: 72%
“…27 More recently, thioether-functionalized hyaluronic acid was electrospun into nanofibres and formed fast-resorbing hydrogels that were highly antioxidant, anti-inflammatory, and significantly promoted wound closure/healing in a diabetic wound model. 28 These data lend support for the expanded use of polysulfides/ PPS as anti-inflammatory agents in topical wound-healing applications. However, slow-degrading crosslinked hydrogels and nanoparticle dispersions are not ideal for inflammatory skin disorders with a more diffuse skin coverage, such as chronic wounds (e.g.…”
Section: Introductionmentioning
confidence: 72%
“…The nCeO 2 -PHBV membranes can enhance cell proliferation and vascularization to promote the healing of diabetic wounds. Liu et al prepared a kind of electrospun thioether-grafted hyaluronic acid nanofibers (FHHA-S/Fe) that can form a nanofibrous hydrogel in situ on the wound, which combine the advantages of both hydrogel and nanofibers [ 237 ]. The in vivo test shows that this material can synergistically modulate the inflammation microenvironment to help diabetic wound healing by scavenging ROS effectively in the early inflammation phase and promoting transformation of the gathered M1 macrophages to the M2 phenotype.…”
Section: Chronic Inflammation-associated Diseases and Therapiesmentioning
confidence: 99%
“…Liu et al reported a resorbable hydrogel composed of electrospun thioether grafted hyaluronic acid nanofibers crosslinked by Fe 3+ ions. [ 26 ] Using a chronic diabetic inflammation mouse model, they found that high‐molecular‐weight hyaluronic acid promoted macrophage polarization into M2 phenotype which secreted anti‐inflammatory and growth factors. [ 96 ] Thioether grafted on hyaluronic acid also scavenged ROS during early stage of inflammation.…”
Section: Hydrogels To Modulate Inflammationmentioning
confidence: 99%
“…StarPEG [62] Hydroexythylcellulose [63] Polyacrylamide [66] Peptide [79] HA [26] Alginate [97] Naturally occurring polymers like hyaluronic acids with inherent anti-inflammatory bioactivity Controlled porosity for inflammatory molecule absorption Optimal porosity and tunable biodegradability for controlled drug release ECM-like feature to improve wound healing Trigger responsive for on-demand drug release Improve cancer immunotherapy PCL-PEG-PCL [100] Piptide [110] Alginate [118] Fibrin [114] Poloxamer 407 [128] Polyvinyl alcohol [119] Betamethasone phosphate [134] Supramolecular prodrug [135] Phase-transition and in situ gel formation (induced by temperature, shear stress, light, ions, etc.) for good injectability Network structures make hydrogels as reservoir to physical encapsulate or chemically link some drug molecules.…”
Section: Modulate Inflammationmentioning
confidence: 99%
See 1 more Smart Citation